The immunostimulant effects of Isochrysis galbana supplemented diet on the spleen of red hybrid tilapia (Oreochromis spp.) evaluated by nuclear magnetic resonance metabolomics - Ahamad Bustamam, Muhammad Safwan; Ahmed Pantami, Hamza; Ahmad Azam, Amalina; Shaari, Khozirah; Min, Chong Chou; Ismail, Intan Safinar (Wiley, 2022)
Significant measures at improving aquaculture health have to be taken since disease outbreaks commonly occur in the fastgrowing aquaculture industry. This study aimed to determine the immunomodulatory properties of an indigenous Malaysian microalgae species, Isochrysis galbana (IG), on red hybrid tilapia (Oreochromis spp.). Then, the potential biomarkers for immunomodulatory properties were identified through metabolic changes in the spleen using the proton nuclear magnetic resonance (1 H NMR) metabolomics approach. IG was cultivated in an indoor annular photobioreactor before being harvested and freeze-dried into dried biomass. The dried IG biomass was incorporated into four experimental diets in concentrations of 0% (diet A), 0.6% (diet B), 1.3% (diet C), 2.5% (diet D), and 5.0% (diet E) basal feed per kg. After 14 days of feeding, diet D has consistently improved the immune responses of innate immunity such as phagocytosis (P > 0:05), respiratory burst (P < 0:05), and lymphoproliferation (P < 0:05) activities which might have helped in maintaining the overall health status of red hybrid tilapia. The orthogonal partial least squares (OPLS) model between diets D and A indicated three important metabolites, namely, isoleucine, glutamate, and tyrosine, have significantly been upregulated when compared to the control. Meanwhile, IG supplementation also resulted in lower concentrations of various metabolites in the spleen including α/βglucose, choline, hypoxanthine, adenosine, and inosine. Hence, the application of metabolomics tools has proved the potential of IG-incorporated fish diet by strongly influencing the metabolic condition in red hybrid tilapia spleen cells and further boosting the immune response and health status in improving aquaculture health.